Coinfection modifies carriage of enzootic and zoonotic parasites in Norway rats from an urban slum. Issue 10 (16th October 2019) - Carvalho‐Pereira, Ticiana S. A.; Souza, Fábio Neves; Santos, Luana Ribeiro do Nascimento; Pedra, Gabriel Ghizzi; Minter, Amanda; Bahiense, Thiago Campanharo; Reis, Mitermayer Galvão; Ko, Albert Icksang; Childs, James E.; da Silva, Eduardo M.; Costa, Federico; Begon, Mike
Abstract: We examine coinfection between helminth species and the bacterium Leptospira interrogans in a natural population of the Norway rat, Rattus norvegicus . We ask whether coinfection can influence the probability and intensity of infection of these enzootic and zoonotic parasites in urban rats, which may affect the loads of parasites excreted into the environment. Rodent sampling was carried out during two seasons in 2014 in a Brazilian urban slum. We sampled rats' feces, kidney imprints, and urine to identify and quantify helminth eggs/larvae and infection by L. interrogans . Eleven species/groups of helminths and L. interrogans were identified among 299 captured rats. Simple correlation tests and generalized linear models were performed to identify general patterns of coinfection and potential direction of effects, respectively, after controlling for consolidated environmental and host biotic variables. Significant associations were illustrated in an interaction network. Focusing on parasites with the potential to cause zoonoses among humans, we observed that coinfection between L. interrogans and the nematode Angiostrongylus cantonensis was significantly more frequent than expected. Reduced prevalence of A. cantonensis was found in the presence of Nippostrongylus brasiliensis, and N. brasiliensis intensities (eggs per gram of feces) were increased with greater intensities of both L. interrogans and Strongyloides sp., the latter of which was, in turn, found to increase the intensities of A. cantonensis . A higher probability of finding L. interrogans was associated with infection by Strongyloides sp. Our study provides a novel perspective on evaluating helminth coinfection profiles in populations of naturally infected urban rats, moving beyond previous studies which have been limited to descriptions of co‐occurrence. Noticeably, infection risk was dependent on coinfection and this should be accounted for when targeting the control of zoonotic pathogens in natural populations.